2023
DOI: 10.1001/jamaophthalmol.2022.6254
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinal Sensitivity Associated With Cotoretigene Toliparvovec in X-Linked Retinitis Pigmentosa With RPGR Gene Variations

Abstract: ImportanceX-linked retinitis pigmentosa (XLRP) is a severe cause of early-onset RP in male individuals, characterized by degeneration of photoreceptors, an extinguished electroretinogram, and vision loss.ObjectiveTo assess the duration of improvements in retinal sensitivity associated with a single, subretinal injection of cotoretigene toliparvovec (BIIB112/AAV8-RPGR) gene therapy after vitrectomy surgery in the dosed eye over 12 months in part 1 of the Clinical Trial of Retinal Gene Therapy for X-linked Retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…To date, RPGR -associated RP clinical trial design has used a single study eye (usually the worse eye) and used the nontreated eye as an internal control. 11 , 12 Variability arising from fatigue could be reduced if only the study eye is tested and a separate cohort is used as a control; however, this strategy would reduce potential sample sizes, which, in rare diseases, may not be feasible. Furthermore, careful consideration of visual function testing order may minimize variability due to fatigue effects; if microperimetry was selected as the primary outcome measure, perhaps this should be completed prior to any other visual function testing, to minimize fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, RPGR -associated RP clinical trial design has used a single study eye (usually the worse eye) and used the nontreated eye as an internal control. 11 , 12 Variability arising from fatigue could be reduced if only the study eye is tested and a separate cohort is used as a control; however, this strategy would reduce potential sample sizes, which, in rare diseases, may not be feasible. Furthermore, careful consideration of visual function testing order may minimize variability due to fatigue effects; if microperimetry was selected as the primary outcome measure, perhaps this should be completed prior to any other visual function testing, to minimize fatigue.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Subsequently, two recent gene therapy trials for RPGR- associated RP have applied a similar criteria as an endpoint for clinical significance, reporting the number of individuals with at least 5 points showing a sensitivity gain of ≥7.0 dB in the treated eye, within the central 16 and 36 loci (when using the 10-2, 68-point testing grid). 11 , 12 Meanwhile, two active RPGR -associated RP clinical trials simply state a change from baseline microperimetry sensitivity as secondary outcome measures without providing more specific endpoint criteria (NCT 03584165 and NCT 03349242). Despite the popularity of microperimetry as an outcome measure in RPGR -associated RP clinical trials, specific endpoint criteria suitability is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…1 The recently completed phase 1 XIRIUS trial has expanded this gene delivery approach to a potential treatment of X-linked retinitis pigmentosa (XLRP), commonly caused by mutations in the retinitis pigmentosa GTPase regulator (RPGR) gene. 2 The phase 1 safety XIRIUS trial evaluated gene therapy using a codon-optimized RPGR gene (cotoretigene toliparvovec [BIIB112/AAV8-RPGR]) that had demonstrated stability and increased levels of RPGR expression in a mouse model. 3 This phase 1 clinical trial included 18 eyes of 18 study participants with a genetically confirmed diagnosis of RPGRmutated XLRP and delivered 6 escalating doses of the vector genome (AAV8-RPGR) combination into the subretinal space using standard vitrectomy techniques.…”
Section: Invited Commentarymentioning
confidence: 99%
“…Management of retinitis pigmentosa and other inherited retinal dystrophies has progressively evolved toward gene therapy, especially after the first successful treatment using an adeno-associated viral vector (AAV8) with gene delivery into retinal photoreceptors . The recently completed phase 1 XIRIUS trial has expanded this gene delivery approach to a potential treatment of X-linked retinitis pigmentosa (XLRP), commonly caused by mutations in the retinitis pigmentosa GTPase regulator (RPGR) gene …”
mentioning
confidence: 99%
“…The Original Investigation titled “Changes in Retinal Sensitivity Associated With Cotoretigene Toliparvovec in X-Linked Retinitis Pigmentosa With RPGR Gene Variations,” published online February 9, 2023, was corrected to fix the spelling of the first nonauthor collaborator’s name on PubMed. This article was corrected online.…”
mentioning
confidence: 99%